Chinggis Khan: Een symbool van superioriteit: De invloed van de Culturele revolutie op de etnische identiteit van de mongolen in Binnen-Mongolië, 1965-1989 - van Aalst, Fleur (Skript Historisch Tijdschrift, 2025)
This article examines the influence of the Chinese Cultural Revolution on the ethnic identity of the Mongols in China. The Cultural Revolution took the shape of an ethnic hunt on the Mongols in the province of Inner Mongolia. This, together with growing Han-Chinese migration to this province, led to rising ethnic tensions. After the Cultural Revolution, the demand for greater autonomy and rectification of the violent period of the Cultural Revolution increased. The more the Mongols were assimilated, the more the demand increased for cultural elements to mark the dividing line between the Mongols and the Han. Chinggis Khan was the layered symbol of this division. He symbolizes a place of remembrance, a lieu de mémoire, through which the Mongols are able to look with pride at a past in which they ruled over the Chinese.